(untitled) (Harmoni, 2021)
Based on the survey results and the National Waqf Literacy Index report that the National Waqf Literacy Index (ILW) value is included in the low category, the importance of wakif literacy for Waqf Pledge Deed Officials (PPAIW) as the front line waqf administration. The focus of this research is to examine the urgency of waqf literacy for officials (PPAIW) who are authorized to carry out the waqf administration process in Indonesia, but have not been optimal in carrying out their duties, causing a lack of anticipation in dealing with waqf disputes. This research uses field research (field research). Primary data sources were taken from in-depth interviews with Waqf Pledge Deed Officials in the area of KUA Beji and KUA Sukmajaya Depok City, East Bogor KUA and North Bogor KUA Bogor City. The results showed that waqf literacy for Waqf Pledge Deed Officials (PPAIW) was included in the low category, which resulted in PPAIW not understanding the excellent service standards for waqf services. The level of satisfaction of the community, Wakif and Nazhir with waqf services, the majority answered they were satisfied with waqf services at KUA, but there were still people who answered that they were not satisfied with waqf services, due to the slow process of waqf and the inactivity of PPAIW in helping to solve waqf administration problems. Strengthening waqf literacy for PPAIW, especially waqf administration, regulation and law, is very important, PPAIW’s weak understanding of waqf administration results in a lack of excellent service and anticipation of waqf disputes, so cases are found such as PPAIW issuing cancellation letters in lieu of waqf pledge deeds (APAIW) which causes legal problems waqf that is protracted, so that the waqf property is not productive (according to its designation).